Improving The Leadership Quality In Disruptive Era: Challenges For Leaders In Government Agencies - Supriyono, (Technium Social Sciences Journal, 2020)
This study aims at answering the research questions of what competencies needed by leaders in the disruptive era, and how to improve the quality of leaders in government agencies. This study uses a phenomenological approach of a qualitative research design. In this study a semi-structured interview is used to understand how participants experienced the phenomenon. The research proved that leaders in the disruptive era have to have a high understanding of VUCA and the changes that have occurred radically. Leaders in the disruptive era must also be agile, more open and willing to communicate and collaborate with various parties. By changing the perspective and attitude, the old leadership style that is no longer suitable for the era of disruption can be changed. This research will contribute significantly benefits and add empirical evidence about leadership related to the disruptive era, for the development of social sciences, especially management and leadership.